Utilization of Solar Panel Energy for electricity in the AT-Taubah Musholla, West Cilebut Village - Ismangil, Agus; Hidayatulah, Syarif; Saepulrohman, Asep (Jurnal Pengabdian Masyarakat Inovatif, 2023)
The AT-Taubah Griya Cilebut Asri 2 Musholla in West Cilebut Village is a place of worship that focuses on its activities in the community to carry out worship, community gatherings, and recitation for children and youth, to increase friendship between West Cilebut village residents, in its activities it needs electricity to support, facilitating residents' activities at the AT-Taubah prayer room, with the application of solar power. making solar panels for use in prayer rooms aims to provide an alternative solution where PLN's electricity facilities are not good or there is no electricity. the results of testing solar panels can be used as an alternative energy where this solar panel utilizes sunlight, namely, to produce electrical energy of 5 volts 125 mA or 0.625 VA.